Cloning of the rDNA repeat unit: An EcoRI fragment spanning the entire nontranscribed spacer region of Neurospora crassa wild type strain 74A - C. Chambers; R. J. Crouch; S. K. Dutta (Fungal Genetics Reports, 1984)
Cloning of the rDNA repeat unit: An EcoRI fragment spanning the entire nontranscribed spacer region of Neurospora crassa wild type strain 74A